'Quantizing international relations': The case for quantum approaches to international theory and security practice. (October 2020) - Der Derian, James; Wendt, Alexander
This special issue is conceived out of the proposition that recent developments in quantum theory as well as innovations in quantum technology have profound implications for international relations, especially in the field of international security. Interaction with quantum theory outside the circle of physics has been limited; our goal is to catalyse an informed debate on the virtues of quantum theory for international relations. As new scientific discoveries and technological applications suggest large-scale quantum phenomena, near-simultaneous interconnectivity creates global entanglements, and ubiquitous media produce profound observer-effects, we wish to make of quantum theory a human science. With the arrival of quantum computing, communications and artificial intelligence, we can also expect to see significant transformations in the nature, production and distribution of power and knowledge. This special issue introduces quantum approaches that can help us better understand, anticipate and perhaps even ameliorate the most pressing global issues facing us today and in the near future.